2022
DOI: 10.1109/jssc.2022.3207907
|View full text |Cite
|
Sign up to set email alerts
|

A 121.4-dB DR Capacitively Coupled Chopper Class-D Audio Amplifier

Abstract: This article presents a class-D amplifier (CDA) with high dynamic range (DR). To eliminate the typically dominant noise contribution of a resistive feedback network, the input and feedback signals are chopped and applied to a capacitive feedback network. However, this leads to high-voltage (HV) transients at the input of the loop filter, which, due to timing and impedance mismatch in the chopped feedback network, could degrade linearity and even overstress low-voltage (LV) core devices. Robust processing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In this paper, on the basis of traditional SDM research, a third-order switching capacitor type SDM is proposed. In addition, the flicker noise and offset voltage generated by the operational amplifier can be modulated to the one, three, and five harmonics of the chopper frequency by chopper stabilization technology [3], and the thermal noise can be eliminated by thermal noise cancellation technology [4]. Finally, it can be filtered by the post filter to further improve the precision of SDM.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, on the basis of traditional SDM research, a third-order switching capacitor type SDM is proposed. In addition, the flicker noise and offset voltage generated by the operational amplifier can be modulated to the one, three, and five harmonics of the chopper frequency by chopper stabilization technology [3], and the thermal noise can be eliminated by thermal noise cancellation technology [4]. Finally, it can be filtered by the post filter to further improve the precision of SDM.…”
Section: Introductionmentioning
confidence: 99%
“…Various power stage classes try to excel in one or both of these two aspects: Class-A stages offer superior linearity at the expense of efficiency; Class-B stages improve on efficiency but suffer from crossover distortion, while Class-AB topologies stay in between Class-A and Class-B in the efficiency metric. Switching output stages like Class-D and its variants, like Class-E (used mostly for RF applications [2]), feature very high power efficiency [3], [4], but lack in linearity compared to their non-switching counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…By changing to a capacitive instead of a resistive feedback network and the application of choppers [12], it was shown that the performance limitations due to resistor noise in the the feedback network can be mitigated reaching a dynamic range in excess of 120 dB.…”
Section: Distortion Due To Feedbackmentioning
confidence: 99%